Reading and self-esteem: a determining link in the learning process - Remache Bunci, Manuel Gonzalo; Burbano Larrea, Burbano Larrea; Cóndor Quimbita, Beatriz Hortencia; Guamán Mejía, Camila Bernarda; Lasluisa Gusqui, María José (Revista Universidad de Guayaquil, 2026)
The objective of this research was to analyze the impact of reading difficulties on the learning process, identifying their causes and challenges. Reading is conceived as a complex activity that integrates various cognitive processes, which may not be fully consolidated due to factors such as a lack of predisposition on the part of teachers and students, the absence of family reinforcement, or genetic influences. The central purpose was to recognize the factors that limit reading learning and propose prevention and strengthening strategies. The methodology adopted a mixed approach. In the quantitative dimension, the Child Neuropsychological Assessment (ENI-2) was applied, an instrument that assesses accuracy, comprehension, and reading speed, which allowed for the collection of relevant and systematic information. In the qualitative dimension, structured interviews were conducted with both teachers and students, which enriched the interpretation of the data. The quantitative results showed that 3rd, 4th, and 5th grade students in General Basic Education have significant difficulties in reading and comprehension, reaching a low average level. In the qualitative dimension, it was found that these difficulties affect self-esteem, which is closely linked to academic performance and the emotional climate generated by teachers and classmates in the classroom. In conclusion, the importance of family participation in the educational process is emphasized, as reinforcing learning at home contributes to the development of reading skills. It is recommended that teaching strategies be implemented that spark interest in reading and strengthen students’ comprehension.